INDO–FRENCH DEFENCE PARTNERSHIP AND REGIONAL SECURITY BALANCE IN SOUTH ASIA - Bharti, Mukesh Shankar (Torun International Studies, 2023)
The article aims to describe the regional security challenges and major threats for India in South Asia. Since 1947, India has been suffering from external security threats such as a form of proxy warfare and terrorism from neighbouring countries. To this purpose, the article also examines recurring issues where India has major border issues with China in the Himalayan terrain to the Eastern region. India has been facing bigger security threats from China and Pakistan in the South Asia region. This article looks at defence cooperation between India and France through the prism of India’s serious security threats in the South Asian region. India’s soft power policy is reflected in a neo-realist approach and expanded by its long-standing defence cooperation with France. Therefore, India has been receiving support from the French government whenever the country needs defence equipment and other assistance. The article uses case studies and discourse analysis methods to answer the questions and draw the main findings and conclusions of the study. Finally, as a result of the study, India’s serious security threats in the South Asian region are pushing the country to purchase defence equipment from France. The relationship between India and France is strengthening bilateral cooperation at a broader level and shaping a strong strategic partnership by uniting in South Asia and the Indo-Pacific as well.